2017
DOI: 10.1111/cas.13343
|View full text |Cite
|
Sign up to set email alerts
|

Mogamulizumab for relapsed adult T‐cell leukemia–lymphoma: Updated follow‐up analysis of phase I and II studies

Abstract: The present study sought to elucidate the prognosis of adult T‐cell leukemia–lymphoma (ATL) patients receiving mogamulizumab, a defucosylated anti‐CCR4 monoclonal antibody. Progression‐free survival (PFS) and overall survival (OS) of ATL patients enrolled in two studies are herein updated, namely NCT00355472 (phase I study of mogamulizumab in relapsed patients with ATL and peripheral T‐cell lymphoma) and NCT00920790 (phase II study for relapsed ATL). Of 13 patients with relapsed aggressive ATL in the phase I s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 48 publications
4
46
1
Order By: Relevance
“…The immunotherapy with Tax peptide-pulsed dendritic cells exhibited efficacy in some ATL patients and is currently under clinical trial (Suehiro et al, 2015). Furthermore, immunomodulatory agents, such as lenalidomide and anti-CCR4 antibodies, are now approved for the treatment of ATL patients (Ishida et al, 2016(Ishida et al, , 2017. Therefore, it will be useful to obtain information not only related to the host genome, but also to the HTLV-1 proviral genome to establish a standardized treatment strategy based on the molecular characteristics of ATL cells.…”
Section: Discussionmentioning
confidence: 99%
“…The immunotherapy with Tax peptide-pulsed dendritic cells exhibited efficacy in some ATL patients and is currently under clinical trial (Suehiro et al, 2015). Furthermore, immunomodulatory agents, such as lenalidomide and anti-CCR4 antibodies, are now approved for the treatment of ATL patients (Ishida et al, 2016(Ishida et al, , 2017. Therefore, it will be useful to obtain information not only related to the host genome, but also to the HTLV-1 proviral genome to establish a standardized treatment strategy based on the molecular characteristics of ATL cells.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, monoclonal antibodies against CD25 have been used to kill Treg cells by antibody‐dependent cell‐mediated cytotoxicity and complement‐mediated cytotoxicity in preclinical and clinical studies alone and in combination with dendritic cell vaccines . Additionally, a monoclonal antibody against the chemokine CCR4, which represents a main promoter of intratumoral Treg cell recruitment, has been tested in phase I/II clinical trials and achieved Treg cell depletion with well‐tolerated antitumor activity, although long‐term effects are unclear . In this context, Gyori et al .…”
Section: Introductionmentioning
confidence: 99%
“…8,24,25 Additionally, a monoclonal antibody against the chemokine CCR4, which represents a main promoter of intratumoral Treg cell recruitment, has been tested in phase I/II clinical trials and achieved Treg cell depletion with well-tolerated antitumor activity, 26 although long-term effects are unclear. 27 In this context, Gyori et al 28 obtained Treg cell depletion in a preclinical in vivo model with a specific Treg deletion of PI3K. They found that isolated disruption of Treg activity had only a limited antitumoral effect and was accompanied by increased numbers of immunosuppressive CSF1R + tumor-associated macrophages within tumor; in contrast, co-depletion of Foxp3 + Treg cells and CSF1R + tumor-associated macrophages increased the recruitment and activity of CD8 + Tconv cells and achieved almost complete tumor rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Although this antibody offers clinical benefit to patients with ATL (9-11), skin-related adverse events (AE) such as erythema multiforme are frequent, and severe AEs including Stevens-Johnson Syndrome/toxic epidermal necrolysis are occasionally observed (12). On the other hand, moderate skin-related AEs after mogamulizumab may be associated with a favorable prognosis (9,13). The skin-related AE may be due to regulatory T (Treg) cell depletion by mogamulizumab (9,12,(14)(15)(16), but the detailed mechanisms have not been fully established.…”
Section: Introductionmentioning
confidence: 99%